La « nostalgie » dans les remontages de Harun Farocki - Amélie Bussy (Conserveries Mémorielles)
Archives images may have inscripted « drownings » (LEVI, 1989) that have taken place in History. That cinema is able to edit them in a way we feel « concerned » with what they filmed is certainly at the heart of Harun Farocki's work around the images of the victims from the nazis camps. In order to observe the poetic means chosen by Farocki to retake their images, this article intend to analyse Farocki's editing as « nostalgic ». Thus, it aims to understand how editing can be a memorial and artistic mean able to write history in order to make appear the fate of the victims at the surface of the screen. In the meantime, it also intends to draw a positive but harsh and sensitive definition of nostalgia since Farocki dares, with it, to reinvent an archive-cinema which also testifies of their irresolvable and definitive disappearance.